2022
DOI: 10.1038/s41524-022-00758-y
|View full text |Cite
|
Sign up to set email alerts
|

Finding predictive models for singlet fission by machine learning

Abstract: Singlet fission (SF), the conversion of one singlet exciton into two triplet excitons, could significantly enhance solar cell efficiency. Molecular crystals that undergo SF are scarce. Computational exploration may accelerate the discovery of SF materials. However, many-body perturbation theory (MBPT) calculations of the excitonic properties of molecular crystals are impractical for large-scale materials screening. We use the sure-independence-screening-and-sparsifying-operator (SISSO) machine-learning algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 110 publications
0
17
0
Order By: Relevance
“… 57 For tetracene, the best dimer extracted from the T1 structure is predicted to yield a SF rate higher than that of the T2 structure (see Figure 6 ), contrary to experimental observations. 57 We note that in the future Simple may be replaced by more advanced models that go beyond the dimer approximations and/or by machine learning models 36 for the evaluation of the SF-based fitness function. The GW+BSE method can capture the many-body effects in a molecular crystal with periodic boundary conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 57 For tetracene, the best dimer extracted from the T1 structure is predicted to yield a SF rate higher than that of the T2 structure (see Figure 6 ), contrary to experimental observations. 57 We note that in the future Simple may be replaced by more advanced models that go beyond the dimer approximations and/or by machine learning models 36 for the evaluation of the SF-based fitness function. The GW+BSE method can capture the many-body effects in a molecular crystal with periodic boundary conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the versatility of the genetic algorithm, different fitness functions can be easily implemented. The SF-based fitness function may be improved in the future by using more advanced models that go beyond the dimer approximation and/or machine learning models . Furthermore, GA fitness functions may be tailored to search for any property or combination of properties of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its obvious indispensability, high-throughput computational material discovery studies for light-matter interaction related applications have rarely incorporated the QP or excitonic properties of materials using GW-BSE formalism [22][23][24][25] mostly due to the unavailability of an automated workflow implementation that can perform such calculations. Two main challenges for such an implementation is the efficient convergence of multiple parameters and the tractability of the huge computational cost associated with the multi-step GW-BSE formalism.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] Based on the experimental and ab initio data set, several research works have reported excellent ML models on the fast prediction of the band gap, evaluation of singlet-triplet energy gap, and fluorescence and phosphorescence rates in reference to the excited state properties. [14][15][16][17][18] The examples are persistent and continue to be applications in various fields. [19][20][21][22] Thermally activated delayed fluorescence (TADF) materials have been regarded as the most promising approach to harnessing 100% efficiency theoretically from the singlet and triplet exciton in organic electronics.…”
Section: Introductionmentioning
confidence: 99%